a DIPLOMASI MODERNISASI DAN KEAMANAN REGIONAL: ANALISIS TERHADAP RELEVANSINYA BAGI NEGARA-NEGARA ISLAM: Negara-negara Islam - Yudha, Gesit; Nirzawan, Fachrizal Dwi (LPPM IAIN Sultan Amai Gorontalo, 2025)
Islamic countries are currently facing two major strategic issues: modernization and regional security. This study aims to examine the relevance of diplomacy in supporting the modernization agenda and maintaining regional security in Islamic countries. The method used is a literature study with a descriptive-analytical methodology and utilizing a critical approach theoretical framework to examine issues such as diplomatic modernization and regional security. The results of the study show that Modernization and regional security are two interrelated and crucial concepts in the development of Islamic countries. Effective modernization encourages regional stability, while regional security is a prerequisite for poverty development. Diplomatic modernization focuses on access to technology, investment, and resources to accelerate economic transformation, while regional security diplomacy builds cooperation in facing threats such as terrorism and conflict. Islamic countries face challenges such as political tensions and technological change, but through this strategic diplomacy, they can turn challenges into development opportunities. Case studies in the United Arab Emirates, Turkey, Saudi Arabia, and Qatar show the effectiveness of the approach in encouraging sustainable development and maintaining regional stability.